Cousins from Overseas: The Labour Market Impact of a Major Forced Return Migration Shock - Lara Bohnet; Susana Peralta; Jo\~ao Pereira dos Santos (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the labour market impact of a major shock of return migration, following the end of the Portuguese Colonial War in 1974. The retornados influx is unique because of its size (half a million people in a country of nine million), and similarity with the native population (almost 80% of the repatriates were Portuguese-born). Relying on rich census data from 1960 and 1981, with individual information on all repatriates, we document a sizeable 15% decrease for native males, and 62% for native females in dependent employment. Men move to self-employment, while women move to inactivity. The bulk of the effects is driven by Portuguese-born repatriates. We propose novel shift-share IVs, based on the repatriates' municipality of birth, and the municipal hotel capacity, exploiting a large-scale resettlement program, and discuss possible mechanisms.
Keywords: F22; J20; R23; 330; return migration; labour market; labour supply; entrepreneurship; instrumental variable